1997
DOI: 10.1002/(sici)1096-9896(199712)183:4<404::aid-path1148>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous loss of E-cadherin and catenins in invasive lobular breast cancer and lobular carcinomain situ

Abstract: Loss of expression of the intercellular adhesion molecule E‐cadherin frequently occurs in invasive lobular breast carcinomas as a result of mutational inactivation. Expression patterns of E‐cadherin and the molecules comprising the cytoplasmic complex of adherens junctions, α‐, β‐ and γ‐catenin, were studied in a series of 38 lobular breast carcinomas with known E‐cadherin mutation status. The effect of loss of E‐cadherin by mutational inactivation (or other mechanisms) on the expression of catenins was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
164
3
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(187 citation statements)
references
References 37 publications
(54 reference statements)
16
164
3
4
Order By: Relevance
“…Other authors have found E-cadherin expression in 0-45% of invasive lobular carcinomas. [59][60][61][62][63][64][65][66][67][68] In these studies no correlation with grade was made. The discrepancy in the literature with regard to the percentage of invasive lobular carcinomas expressing E-cadherin may relate to differences between the populations studied, sensitivity and specificity of the antibodies used and diagnostic variation as applied to lobular carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have found E-cadherin expression in 0-45% of invasive lobular carcinomas. [59][60][61][62][63][64][65][66][67][68] In these studies no correlation with grade was made. The discrepancy in the literature with regard to the percentage of invasive lobular carcinomas expressing E-cadherin may relate to differences between the populations studied, sensitivity and specificity of the antibodies used and diagnostic variation as applied to lobular carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…For the evaluation of E-cadherin expression, we used previously published criteria. 31,49 The intensity of immunohistochemical staining in tumor cells was estimated semiquantitatively by comparison with normal pre-existing epithelial cells in the same section as an internal control. If the staining intensity of tumor cells was the same as that of normal epithelial cells, E-cadherin was considered as "preserved expression" (ϩϩ).…”
Section: Discussionmentioning
confidence: 99%
“…Since their original description, variants of lobular carcinoma in situ have been recognized, aided by differential E-cadherin immunostaining. [3][4][5] These variants include pleomorphic lobular carcinoma in situ characterized by discohesive pleomorphic cells with abundant cytoplasm. 6 Rosen described 'florid' lobular carcinoma in situ characterized by 'tumor cells that fill and expand the duct lumen' that 'may develop central necrosis and calcifications'.…”
mentioning
confidence: 99%